Public health education: the status of health and health-related physical activity courses in Texas community colleges - Ladd, Garry G. (Frontiers in Public Health, 2023)
Background There is an inverse relationship between disease and both health literacy and physical literacy. Courses taken during the completion of degrees at community colleges help to prepare students to be productive members of society by teaching knowledge, skills, and abilities needed for employment and good citizenship. Coursework in public health education and health-related behaviors should be included in the overall community college curriculum. The purpose of this study was to determine the status of Health/Wellness/Physical Fitness Lecture (HWPFL) and Health-Related Physical Activity (HRPA) courses in Texas community colleges. Methods A review of the institutional websites of Texas community colleges (N = 50) was performed to access information regarding HWPFL and HRPA courses and graduation requirements. Information regarding the Texas Core Curriculum was reviewed for any local additions to the state mandated requirements that students are required to complete prior to the attainment of Associate in Arts (AA) and Associate in Science (AS) degrees. Results Individual colleges were grouped into those with <5,000 students (N = 21), those having 5,000–10,000 students (N = 16), and those with >10,000 students (N = 13). Three (6%) institutions require a HWPFL course for AA and AS degrees and 49 (98%) had such courses available for elective credit. Two (4%) colleges require an HRPA course for AA and AS degrees whereas 47 (94%) offer such courses for elective credit. There was one college that only offers a HWPFL course. One college did not offer either HWPFL or HRPA courses. There were many identical courses offered by various colleges for required and elective credit. Conclusion Requiring health, wellness, and health-related physical activity requirements in Texas community colleges can be a policy solution for improving health and physical literacy in students. This research study demonstrated the prevalence of health, wellness, and health-related physical activity requirements in the 50 public community colleges in the state of Texas. Offering courses in health, wellness, and health-related physical activity as required or elective courses for graduation from Texas community colleges is a means through which to develop health literacy and physical literacy in students resulting in a positive influence on public health.